All-solid-state optical energy storage integrated device and preparation method and application thereof

Through the integrated optical energy storage device with all solid state design, the characteristics of dye-sensitized batteries and lithium-sulfur batteries are integrated, and the combination of gel electrolytes and β-cyclodextrins, multiple problems of existing photorechargeable batteries and lithium-sulfur batteries are solved, achieving efficient photoelectric conversion and energy storage.

CN119627203APending Publication Date: 2025-03-14SHANTOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449042.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing photorechargeable batteries have problems such as high ohmic loss, low energy conversion efficiency, strong volatility of liquid electrolytes, poor safety and stability, and traditional lithium-sulfur batteries have insufficient discharge performance in dark environments.

Method used

The integrated photoelectric energy storage devices adopt an all-solid-state design, including energy storage electrodes, energy storage all-solid-state electrolytes, compatible electrodes, photoelectric conversion all-solid-state electrolytes and dye-sensitized photoanodes, are used to integrate the photoelectric conversion function of dye-sensitized batteries and the high capacity characteristics of lithium-sulfur batteries, and combine gel electrolytes and β-cyclodextrin to improve the photoelectric conversion efficiency and energy storage density of the battery.

Benefits of technology

It significantly improves the photoelectric conversion efficiency and discharge specific capacity of the battery, solves the volatility problem of liquid electrolyte, improves the safety and stability of the battery, and achieves more efficient energy storage and release under light-assisted conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627203A_ABST
    Figure CN119627203A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy conversion and storage devices, and particularly discloses an all-solid-state optical energy storage integrated device and a preparation method and application thereof. The all-solid-state optical energy storage integrated device sequentially comprises an energy storage electrode, an energy storage all-solid-state electrolyte, a compatible electrode, a photoelectric conversion all-solid-state electrolyte and a dye-sensitized photoanode from bottom to top, wherein the compatible electrode comprises foamed nickel and a carbon-sulfur composite material coated on the foamed nickel, the preparation raw materials of the energy storage all-solid-state electrolyte comprise polyoxyethylene, lithium bis (trifluoromethanesulfonimide) and beta-cyclodextrin, and the preparation raw materials of the photoelectric conversion all-solid-state electrolyte comprise polyoxyethylene, elemental iodine, lithium iodide and beta-cyclodextrin. And the energy storage electrode is a lithium metal anode. The photoelectric conversion unit and the energy storage unit are integrated in one device, efficient light energy conversion and electric energy storage are achieved, and good energy conversion efficiency and cycling stability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy conversion and storage devices, and in particular relates to an all-solid-state optical energy storage integrated device and a preparation method and application thereof. Background Art

[0002] As the global demand for renewable energy increases, the development of efficient and stable energy storage devices has become an important research direction. Among the many energy storage technologies, photorechargeable batteries have attracted widespread attention because they can directly convert solar energy into electrical energy and store it. This type of battery imitates photosynthesis in nature and converts solar energy into chemical energy through photoelectrochemical reactions, providing a new solution for modern energy systems.

[0003] At present, photorechargeable batteries mainly rely on connecting solar cells and energy storage devices (such as batteries or capacitors) in the form of external circuits. This "off-grid" system usually requires additional space to accommodate two sets of equipment, and there are significant ohmic losses in the circuit connection. In addition, the voltage mismatch problem between traditional solar cells and energy storage devices leads to low energy conversion efficiency, limiting its widespread application. On the other hand, lithium-sulfur batteries, as a new generation of high-energy density batteries, have attracted attention due to their high theoretical specific capacity (1675mAh / g) and abundant sulfur resources. However, there are multiple challenges in the practical application of lithium-sulfur batteries, especially the volatility of liquid electrolytes. This not only affects the safety and stability of the battery, but also leads to capacity decay in long-term use. In addition, the discharge performance of traditional lithium-sulfur batteries in dark environments needs to be improved.

[0004] In order to overcome these challenges, researchers began to explore the application of solid-state electrolytes. All-solid-state electrolytes can not only effectively reduce the volatilization of electrolytes and improve battery safety, but also provide better ionic conductivity and improve the battery's cycle performance. However, the current all-solid-state electrolytes still need to be improved in terms of photoelectric conversion and storage efficiency. Therefore, scholars began to think about how to effectively combine photoelectric conversion with energy storage and develop efficient and stable all-solid-state electrolytes. Polyethylene oxide (PEO)-based solid electrolytes have attracted widespread attention from scholars because of their ether-based repeating units with excellent lithium ion transmission capabilities. They are currently the most studied and widely used polymer solid electrolytes. However, PEO has a high degree of crystallinity, which means that PEO solid electrolytes still have problems such as low ionic conductivity and poor high-voltage stability. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes an all-solid-state integrated light energy storage device and its preparation method and application. The all-solid-state design of the device not only improves the mechanical strength and durability, enhances the chemical stability and safety, but also optimizes the photoelectric conversion efficiency and energy storage density, and realizes efficient light energy conversion and electrical energy storage.

[0006] The inventive concept of the present invention is as follows: the all-solid-state photo-energy storage integrated device proposed in the present invention includes energy storage electrode, energy storage all-solid-state electrolyte, compatible electrode, photoelectric conversion all-solid-state electrolyte and dye-sensitized photoanode from bottom to top, wherein: energy storage electrode, energy storage all-solid-state electrolyte and compatible electrode constitute energy storage module; compatible electrode, photoelectric conversion all-solid-state electrolyte and dye-sensitized photoanode constitute photoelectric conversion module; by integrating the photoelectric conversion function of dye-sensitized battery and the high capacity characteristics of lithium-sulfur battery, combined with all-solid-state electrolyte, the photoelectric conversion efficiency and discharge specific capacity of the battery are significantly improved. This structural design not only solves the volatility problem of liquid electrolyte, but also realizes more efficient energy storage and release under light-assisted conditions, opening up a new path for photoelectric conversion and energy storage technology.

[0007] At the same time, the present invention adopts gel electrolyte as the all-solid electrolyte electrolyte structure, which enhances the electrochemical stability and safety, and avoids the leakage and volatilization problems of traditional liquid electrolytes; and the all-solid electrolyte adds β-cyclodextrin (β-CD) to improve the energy conversion efficiency and cycle stability of the device. The compatible electrode uses nickel foam as a carrier, and utilizes the good conductivity, electrocatalysis and structural stability of nickel foam to improve the energy density, power density and cycle stability of the battery; the carbon-sulfur composite material is used as a bifunctional compatible electrode, and as the positive electrode material of the lithium-sulfur battery and the counter electrode of the solar cell, it has high conductivity and structural stability; and sulfur as the main electrode material has a higher theoretical capacity, which gives the light-charged lithium-sulfur battery a higher specific capacity. In addition, the all-solid-state design of the device improves the mechanical strength and durability, and optimizes the photoelectric conversion efficiency and energy storage density, which is suitable for a variety of application scenarios such as portable electronic devices and wearable devices.

[0008] In order to solve the above technical problems, the first aspect of the present invention provides an all-solid-state optical energy storage integrated device, which includes, from bottom to top, an energy storage electrode, an energy storage all-solid-state electrolyte, a compatible electrode, a photoelectric conversion all-solid-state electrolyte and a dye-sensitized photoanode;

[0009] The compatible electrode includes nickel foam and a carbon-sulfur composite material coated on the nickel foam, the raw materials for preparing the energy storage all-solid-state electrolyte include polyethylene oxide, lithium bistrifluoromethanesulfonyl imide (LiTFSI) and β-cyclodextrin, the raw materials for preparing the photoelectric conversion all-solid-state electrolyte include polyethylene oxide, elemental iodine, lithium iodide and β-cyclodextrin, and the energy storage electrode is a lithium metal anode.

[0010] Specifically, the present invention designs a light-assisted charging lithium-sulfur integrated device based on a three-electrode system, including a dye-sensitized photoanode, a carbon-sulfur composite material (S / C) loaded on nickel foam as a compatible electrode and a lithium metal anode. Among them, the S / C electrode is a dual-functional compatible electrode, and is also used as a positive electrode material for lithium-sulfur batteries and a counter electrode for solar cells, with high conductivity and structural stability; at the same time, the S / C compatible electrode selects nickel foam as a carrier, and utilizes the good conductivity, electrocatalysis and structural stability of nickel foam to help improve the energy density, power density and cycle stability of the battery. These characteristics play a vital role in the generation and conversion of polysulfides in lithium-sulfur batteries and the improvement of overall battery performance, and nickel foam, as a p-type oxide semiconductor with a high work function, has a hole transport layer material with electron blocking properties. The dye-sensitized photoelectrode uses an energy storage all-solid electrolyte based on PEO-β-CD-LiI, which can greatly increase the working time of the dye-sensitized layer. Sulfur, as the main electrode material, has a high theoretical capacity, which can give the light-charged lithium-sulfur battery (PRSB) a higher specific capacity.

[0011] At the same time, the present invention uses a three-electrode system that is beneficial to the separation of photogenerated carriers and maintains the integrity of the battery performance; and the energy storage all-solid-state electrolyte (PEO-β-CD-LiI) is used in the three-electrode system (PRB), which simplifies the assembly process and enhances compatibility. Under illumination, the holes generated by the dye-sensitized photoanode promote the oxidation of lithium polysulfide in the electrolyte, effectively reducing the charging voltage, and the additional photogenerated electrons increase the specific capacity of the PRSB under illumination. This solves the incompatibility problem of integrated PRBs and provides a new strategy for improving the specific capacity of PRBs and the practical application of PRBs.

[0012] In some embodiments of the present invention, the method for preparing the compatible electrode comprises the following steps:

[0013] (1) mixing a sulfur source, a carbon source and polyvinylidene fluoride in a first organic solvent and grinding the mixture to obtain a slurry;

[0014] (2) Apply the slurry to the foam The compatible electrode is obtained by sequentially performing heat treatment and compaction treatment.

[0015] In some embodiments of the present invention, in step (1), the sulfur source includes sublimated sulfur.

[0016] In some embodiments of the present invention, in step (1), the carbon source includes Ketjen black and carbon nanotubes.

[0017] In some embodiments of the present invention, the mass ratio of Ketjen black to carbon nanotubes is (0.5-1.5):1.

[0018] In some embodiments of the present invention, in step (1), the first organic solvent comprises N-methylpyrrolidone (NMP).

[0019] In some embodiments of the present invention, in step (1), the mass ratio of the sulfur source, the carbon source and polyvinylidene fluoride is (6-8):(1-3):1.

[0020] In some embodiments of the present invention, in step (1), the mass volume ratio of the polyvinylidene fluoride to the first organic solvent is 1 g: (4-6) mL.

[0021] In some embodiments of the present invention, in step (2), the heat treatment is performed at 70-90° C. for 10-14 hours.

[0022] In some embodiments of the present invention, in step (2), the pressure of the compaction treatment is 5-15 MPa.

[0023] In some embodiments of the present invention, the method for preparing the photoelectric conversion all-solid electrolyte comprises the following steps:

[0024] Elemental iodine and lithium iodide are dissolved in a second organic solvent, then beta-cyclodextrin is added and mixed, and then polyethylene oxide is added, stirred under heating conditions, and dried to obtain the photoelectric conversion all-solid electrolyte.

[0025] In some embodiments of the present invention, the second organic solvent comprises acetonitrile.

[0026] In some embodiments of the present invention, the raw materials for preparing the photoelectric conversion all-solid electrolyte include, by weight: 0.5-2 parts of elemental iodine, 3-8 parts of lithium iodide, 1-2 parts of β-cyclodextrin, and 6-9 parts of polyethylene oxide.

[0027] In some embodiments of the present invention, the mass volume ratio of the polyethylene oxide to the second organic solvent is 1 g: (8-12) mL.

[0028] In some embodiments of the present invention, the heating condition is stirring at 50-70° C. for 4-6 hours.

[0029] In some embodiments of the present invention, the method for preparing the energy storage all-solid-state electrolyte comprises the following steps: dissolving polyethylene oxide in the second solvent, heating and stirring; then adding β-cyclodextrin and continuing stirring; then adding lithium bistrifluoromethanesulfonyl imide and drying to obtain.

[0030] In some embodiments of the present invention, the raw materials for preparing the energy storage all-solid-state electrolyte include, by weight: polyethylene oxide, lithium bis(trifluoromethanesulfonyl imide) and β-cyclodextrin in a mass ratio of 1:(0.2-0.4):(0.1-0.3).

[0031] In some embodiments of the present invention, the heating condition is stirring at 50-70° C. for 1-3 hours.

[0032] In some embodiments of the present invention, the drying condition is drying at 50-70° C. for 5-6 hours.

[0033] The second aspect of the present invention provides a method for preparing the above-mentioned all-solid-state optical energy storage integrated device, characterized in that it comprises the following steps:

[0034] The energy storage electrode, the energy storage all-solid electrolyte, the compatible electrode, the photoelectric conversion all-solid electrolyte and the dye-sensitized photoanode are stacked and assembled from bottom to top to obtain the all-solid-state optical energy storage integrated device.

[0035] The third aspect of the present invention provides the application of the above-mentioned all-solid-state integrated optical energy storage device in portable electronic devices or wearable devices.

[0036] In some embodiments of the present invention, the portable electronic device includes a mobile phone, a computer, a digital camera, a mobile power source, etc.

[0037] In some embodiments of the present invention, the wearable device includes a smart bracelet, a smart watch, smart glasses, a heart rate monitoring bracelet, a smart headset, etc.

[0038] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0039] (1) The all-solid-state photo-energy storage integrated device proposed in the present invention includes, from bottom to top, an energy storage electrode, an energy storage all-solid-state electrolyte, a compatible electrode, a photoelectric conversion all-solid-state electrolyte, and a dye-sensitized photoanode, wherein: the energy storage electrode, the energy storage all-solid-state electrolyte, and the compatible electrode constitute an energy storage module; the compatible electrode, the photoelectric conversion all-solid-state electrolyte, and the dye-sensitized photoanode constitute a photoelectric conversion module; by integrating the photoelectric conversion function of the dye-sensitized battery and the high capacity characteristics of the lithium-sulfur battery, combined with the all-solid-state electrolyte, the photoelectric conversion efficiency and discharge specific capacity of the battery are significantly improved. This structural design not only solves the volatility problem of the liquid electrolyte, but also realizes more efficient energy storage and release under light-assisted conditions, opening up a new path for photoelectric conversion and energy storage technology.

[0040] (2) The compatible electrode of the present invention uses nickel foam as a carrier, and utilizes the good conductivity, electrocatalysis and structural stability of nickel foam to improve the energy density, power density and cycle stability of the battery; the carbon-sulfur composite material is used as a bifunctional compatible electrode, and as a positive electrode material for lithium-sulfur batteries and a counter electrode for solar cells, and has high conductivity and structural stability; and sulfur, as the main electrode material, has a higher theoretical capacity, which can give the photorechargeable lithium-sulfur battery a higher specific capacity.

[0041] (3) The present invention applies the energy storage all-solid electrolyte PEO-β-CD-LiI in a three-electrode system, which simplifies the assembly process and enhances compatibility. Under light, the holes generated by the dye-sensitized photoanode promote the oxidation of lithium polysulfide in the electrolyte, effectively reducing the charging voltage, and the additional photogenerated electrons increase the specific capacity of PRSB under light. This solves the incompatibility problem of integrated PRBs and provides a new strategy for improving the specific capacity of PRBs and the practical application of PRBs. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a structural diagram of the all-solid-state optical energy storage integrated device prepared in Example 1;

[0043] Figure 2 The light-dark alternating chronopotentiogram of the all-solid-state integrated optical energy storage device prepared in Example 1 at a current density of 1C;

[0044] Figure 3 The charge and discharge curves of the all-solid-state integrated optical energy storage device prepared in Example 1 at different discharge current densities under light charging conditions;

[0045] Figure 4 The charge and discharge curves of the all-solid-state integrated optical energy storage device prepared in Example 1 under different discharge current densities under dark charging conditions;

[0046] Figure 5JV curves of the dye-sensitized solar cell modules prepared in Example 2 and Comparative Example 1;

[0047] Figure 6 The infrared analysis spectra of the photoelectric conversion all-solid electrolytes prepared in Example 2 and Comparative Example 1;

[0048] Figure 7 This is a scanning electron microscope image of the photoelectric conversion all-solid electrolyte prepared in Comparative Example 1;

[0049] Figure 8 A scanning electron microscope image of the photoelectric conversion all-solid electrolyte prepared in Example 2;

[0050] Fig. 9 The cross-sectional scanning electron microscope image and energy spectrum analysis image of the photoelectric conversion all-solid electrolyte prepared in Example 2;

[0051] Fig.10 This is a scanning electron microscope image of the counter electrode prepared in Example 2 before being coated with the carbon-sulfur material;

[0052] Fig.11 This is a scanning electron microscope image of the counter electrode prepared in Example 2 after being coated with a carbon-sulfur material;

[0053] Fig.12 The cross-sectional scanning electron microscope image and energy spectrum analysis image of the counter electrode prepared in Example 2;

[0054] Fig.13 The long cycle performance of the lithium-sulfur battery modules prepared in Example 3 and Comparative Example 2 at a current density of 0.1C;

[0055] Fig.14 The long cycle performance of the lithium-sulfur battery modules prepared in Example 3 and Comparative Example 2 at a current density of 0.2C;

[0056] Fig.15 This is a graph showing the constant current charge and discharge test results of the lithium-sulfur battery modules prepared in Example 4 and Comparative Example 3. DETAILED DESCRIPTION

[0057] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0058] Example 1

[0059] A method for preparing an all-solid-state optical energy storage integrated device comprises the following steps:

[0060] (1) 0.635 g of lithium iodide and 0.127 g of elemental iodine were dissolved in 10 mL of acetonitrile, and 0.15 g of β-cyclodextrin was added and mixed evenly. Then 1 g of polyethylene oxide was added and stirred at 60 ° C for 5 h. Finally, it was dried at 60 ° C to obtain a photoelectric conversion all-solid electrolyte (PEO / β-CD / LiI / I2).

[0061] (2) First, the nickel foam was cut and washed several times to remove the contaminants on the surface, and used as the electrode material current collector. 0.7 g of sublimated sulfur, 0.1 g of carbon nanotubes, 0.1 g of Ketjen black, and 0.1 g of PVDF were mixed in 5 mL of NMP and ground in an agate mortar for 10 min. The slurry was applied to the center of the nickel foam, and the electrode material coverage area was controlled to be 1 cm 2 . It was then placed in an oven at 80°C for 12 hours (the S / C electrode was covered with a petri dish to prevent the loss of sulfur), and the average mass of sulfur loaded on the S / C electrode was calculated to be about 2.0 mg by weighing. In order to ensure close contact between the active material and the current collector, the sulfur-carbon nanotube composite (S / C) electrode was compacted with a pressure of 10 MPa before device assembly to serve as a compatible electrode.

[0062] (3) 0.4 g of ethyl cellulose, 3.2 g of α-pinene alcohol and 0.8 g of P25 titanium dioxide nanoparticles were added to 8 mL of ethanol and mixed. After 6 h of ultrasonication, the mixture was stirred for 30 min until it became a gel to obtain TiO2 slurry. Next, the FTO was ultrasonically cleaned and dried with ethanol, acetone and deionized water in turn. The FTO was placed on a sizing machine and spin-coated with TiO2 slurry. After spin coating, it was dried for 12 h to remove the pinene alcohol in the photoanode. Then it was placed in a muffle furnace at 450 ° C for 30 min. After cooling to room temperature, the preparation of the TiO2 photoanode was completed. Finally, 18 mg of N719 dye was weighed and dispersed in 50 mL of ethanol solution, placed in a dark environment and stirred for 24 h, and then the TiO2 photoanode was immersed in the dye solution in the dark for 24 h. After being taken out, it was washed with ethanol and blown dry, and then stored in a dark environment to obtain a dye-sensitized photoanode.

[0063] (4) Dissolve 1 g of polyethylene oxide in 10 mL of acetonitrile, heat and stir at 60 °C for 4 h, add 0.2 g of β-cyclodextrin, continue stirring at 60 °C for 2 h, add 0.3 g of lithium bis(trifluoromethanesulfonylimide) and place in an oven at 60 °C for 6 h to obtain an energy storage all-solid-state electrolyte (PEO / LiTFSI / β-CD).

[0064] (5) Using lithium metal electrode as energy storage electrode.

[0065] (6) The energy storage electrode, energy storage all-solid electrolyte, compatible electrode, photoelectric conversion all-solid electrolyte and dye-sensitized photoanode prepared above are stacked from bottom to top to assemble an all-solid-state photo-energy storage integrated device. The specific assembly process is as follows: dye-sensitized TiO2 photoanode, S / C compatible electrode and lithium metal negative electrode. First, the dye-sensitized TiO2 photoanode is connected to copper foil as a conductor, and the polyimide tape is cut into a 2cm×2cm outer circle and a 1cm×1cm inner circle. The polyimide tape is covered on the FTO that is not covered with dye-sensitized TiO2 to prevent the photoanode and the counter electrode from contacting and causing a short circuit in the device. The photoelectric conversion all-solid electrolyte is also cut into 2cm×2cm. After the FTO glass cut into 2cm×2cm is prepared, a layer of copper foil is covered on the FTO surface to serve as the current collector of the lithium electrode. The prepared TiO2 photoanode, S / C compatible electrode, energy storage all-solid electrolyte and lithium metal negative electrode current collector were transferred to the inside of the glove box filled with argon. The lithium sheet was first fixed on the FTO wrapped in copper foil, and the photoelectric conversion all-solid electrolyte was placed on the dye-sensitized TiO2 photoanode. The S / C compatible electrode was placed on top, and then the energy storage all-solid electrolyte was placed, and then the lithium sheet negative electrode was placed. The three electrodes of the integrated device were clamped and compacted with a binder clip, and the device was sealed with a hot melt gun, and the target device was successfully assembled.

[0066] Example 2

[0067] A method for preparing a dye-sensitized solar cell module comprises the following steps:

[0068] (1) 0.635 g of lithium iodide and 0.127 g of elemental iodine were dissolved in 10 mL of acetonitrile organic solvent, and then 0.03 g, 0.05 g, 0.07 g, 0.1 g, and 0.15 g of β-cyclodextrin (the mass percentages correspond to 3%, 5%, 7%, 10%, and 15%, respectively) were added, mixed evenly, and then 1 g of polyethylene oxide was added. The mixture was stirred at 60° C. for 5 h, and finally dried at 60° C. to obtain a photoelectric conversion all-solid electrolyte (PEO / β-CD / LiI / I2).

[0069] (2) First, the nickel foam was cut and washed several times to remove the contaminants on the surface, and used as the electrode material current collector. 0.7 g of sublimated sulfur, 0.1 g of carbon nanotubes, 0.1 g of Ketjen black, and 0.1 g of PVDF were mixed in 5 mL of NMP and ground in an agate mortar for 10 min. The slurry was applied to the center of the nickel foam, and the electrode material coverage area was controlled to be 1 cm 2. It was then placed in an oven at 80°C for 12 hours (the S / C electrode was covered with a petri dish to prevent the loss of sulfur), and the average mass of sulfur loaded on the S / C electrode was calculated to be about 2.0 mg by weighing. In order to ensure close contact between the active material and the current collector, the sulfur-carbon nanotube composite (S / C) electrode was compacted with a pressure of 10 MPa before device assembly to serve as the counter electrode.

[0070] (3) 0.4 g of ethyl cellulose, 3.2 g of α-pinene alcohol and 0.8 g of P25 titanium dioxide nanoparticles were added to 8 mL of ethanol and mixed. After 6 h of ultrasonication, the mixture was stirred for 30 min until it became a gel to obtain TiO2 slurry. Next, the FTO was ultrasonically cleaned and dried with ethanol, acetone and deionized water in turn. The FTO was placed on a sizing machine and spin-coated with TiO2 slurry. After spin coating, it was dried for 12 h to remove the pinene alcohol in the photoanode. Then it was placed in a muffle furnace at 450 ° C for 30 min. After cooling to room temperature, the preparation of the TiO2 photoanode was completed. Finally, 18 mg of N719 dye was weighed and dispersed in 50 mL of ethanol solution, placed in a dark environment and stirred for 24 h, and then the TiO2 photoanode was immersed in the dye solution in the dark for 24 h. After being taken out, it was washed with ethanol and blown dry, and then stored in a dark environment to obtain a dye-sensitized photoanode.

[0071] (4) The counter electrode, photoelectric conversion all-solid electrolyte and dye-sensitized photoanode prepared above are stacked in sequence from bottom to top to assemble a dye-sensitized solar cell module.

[0072] Example 3

[0073] A method for preparing a lithium-sulfur battery module comprises the following steps:

[0074] (1) 1 g of polyethylene oxide was dissolved in 10 mL of acetonitrile, heated and stirred at 60 ° C for 4 h, and then 0.2 g of β-cyclodextrin was added. The mixture was stirred at 60 ° C for 2 h, and then 0.3 g of lithium bis(trifluoromethanesulfonylimide) was added and placed in an oven at 60 ° C for 6 h to obtain an energy storage all-solid electrolyte (PEO / LiTFSI / β-CD).

[0075] (2) First, the nickel foam was cut and washed several times to remove the contaminants on the surface, and used as the electrode material current collector. 0.7 g of sublimated sulfur, 0.1 g of carbon nanotubes, 0.1 g of Ketjen black, and 0.1 g of PVDF were mixed in 5 mL of NMP and ground in an agate mortar for 10 min. The slurry was applied to the center of the nickel foam, and the electrode material coverage area was controlled to be 1 cm 2. It was then placed in an oven at 80°C for 12 hours (the S / C electrode was covered with a petri dish to prevent the loss of sulfur), and the average mass of sulfur loaded on the S / C electrode was calculated to be about 2.0 mg by weighing. In order to ensure close contact between the active material and the current collector, the sulfur-carbon nanotube composite (S / C) electrode was compacted at a pressure of 10 MPa before device assembly as an energy storage electrode.

[0076] (3) The energy storage electrode, energy storage all-solid electrolyte and lithium electrode prepared above are stacked in sequence from bottom to top to assemble a "sandwich structure" lithium-sulfur battery module.

[0077] Example 4

[0078] A method for preparing a lithium-sulfur battery module comprises the following steps:

[0079] (1) 1 g of polyethylene oxide was dissolved in 10 mL of acetonitrile, heated and stirred at 60 ° C for 4 h, then 0.2 g of β-cyclodextrin was added, and the mixture was stirred at 60 ° C for 4 h. Then 0.2 g of lithium bis(trifluoromethanesulfonylimide) was added and placed in an oven at 60 ° C for drying for 6 h. Then 0.3 g of lithium bis(trifluoromethanesulfonylimide) was added and placed in an oven at 60 ° C for drying for 6 h to obtain an energy storage all-solid-state electrolyte (PEO / LiTFSI / β-CD).

[0080] (2) First, the nickel foam was cut and washed several times to remove the contaminants on the surface, and used as the electrode material current collector. 0.7 g of sublimated sulfur, 0.1 g of carbon nanotubes, 0.1 g of Ketjen black, and 0.1 g of PVDF were mixed in 5 mL of NMP and ground in an agate mortar for 10 min. The slurry was applied to the center of the nickel foam, and the electrode material coverage area was controlled to be 1 cm 2 . It was then placed in an oven at 80°C for 12 hours (the S / C electrode was covered with a petri dish to prevent the loss of sulfur), and the average mass of sulfur loaded on the S / C electrode was calculated to be about 2.0 mg by weighing. In order to ensure close contact between the active material and the current collector, the sulfur-carbon nanotube composite (S / C) electrode was compacted at a pressure of 10 MPa before device assembly as an energy storage electrode.

[0081] (3) The energy storage electrode, energy storage all-solid electrolyte and lithium electrode prepared above are stacked in sequence from bottom to top to assemble a "sandwich structure" lithium-sulfur battery module.

[0082] Comparative Example 1

[0083] The only difference between Comparative Example 1 and Example 2 is that the raw materials for preparing the photoelectric conversion all-solid-state electrolyte in step (1) are different, specifically: 0.635 g of lithium iodide and 0.127 g of elemental iodine are dissolved in 10 mL of acetonitrile, mixed evenly, and then 1 g of polyethylene oxide is added, stirred at 60°C for 5 h, and finally dried at 60°C to obtain a photoelectric conversion all-solid-state electrolyte (PEO / LiI / I2).

[0084] Comparative Example 2

[0085] The only difference between Comparative Example 2 and Example 3 is that the raw materials for preparing the energy storage all-solid-state electrolyte in step (1) are different, specifically: 1 g of polyethylene oxide is dissolved in 10 mL of acetonitrile, heated and stirred at 60 ° C for 4 h, and then 0.3 g of lithium bis(trifluoromethanesulfonyl imide) is added and placed in an oven at 60 ° C for 6 h to obtain an energy storage all-solid-state electrolyte (PEO / LiTFSI).

[0086] Comparative Example 3

[0087] The difference between Comparative Example 3 and Example 4 is that the raw materials for preparing the energy storage electrode in step (2) are different. Specifically, the nickel foam is first cut and washed several times to remove the pollutants on the surface, and used as the electrode material current collector. 0.7g of sublimated sulfur, 0.2g of acetylene black and 0.1g of PVDF are mixed in 5mL of NMP, ground in an agate mortar for 10min, and the slurry is applied to the center of the nickel foam, and the electrode material coverage area is controlled to be 1cm 2 . It was then placed in an oven at 80°C for 12 hours (the S / C electrode was covered with a petri dish to prevent the loss of sulfur), and the average mass of sulfur loaded on the S / C electrode was calculated to be about 2.0 mg by weighing. In order to ensure close contact between the active material and the current collector, the sulfur-carbon nanotube composite (S / C) electrode was compacted at a pressure of 10 MPa before device assembly as an energy storage electrode.

[0088] Performance Testing

[0089] Figure 1 This is a schematic diagram of the structure of the all-solid-state optical energy storage integrated device prepared in Example 1. The device includes, from bottom to top, an energy storage lithium metal electrode (Li metal electrode), an energy storage all-solid-state electrolyte, an S / C compatible electrode (S / Celectrode), a photoelectric conversion all-solid-state electrolyte (All solid electroyte) and a dye-sensitized photoanode (Photoanode).

[0090] Figure 2This is a chronopotentiometric diagram of the all-solid-state integrated optical energy storage device prepared in Example 1 at a current density of 1C. In the figure, the horizontal axis Time represents time, the left vertical axis Voltage represents voltage, and the right vertical axis Specific Capacity represents specific capacity. Figure 2 It can be seen that under a discharge rate of 1C, the all-solid-state optical energy storage integrated device assembled by the present invention can stably cycle 24 times; at the same time, compared with dark charging, the battery discharge specific capacity under light charging conditions is increased by about 100mAh / g.

[0091] Figure 3 and Figure 4 The following are the charge and discharge curves of the all-solid-state integrated optical energy storage device prepared in Example 1 under different discharge current densities under light charging (Charge W / illumination) and dark charging (Charge W / O illumination) conditions. In the figure, the horizontal axis Capacity represents the capacity, and the vertical axis Voltage represents the voltage. Figure 3-4 It can be seen that the device can stably perform charge and discharge cycles even under large currents.

[0092] Figure 5 The JV curves of the dye-sensitized solar cell modules prepared in Example 2 and Comparative Example 1, in which the horizontal axis Voltage represents the voltage, and the vertical axis Current Density represents the current density. It is calculated that the photoelectric conversion efficiency of the dye-sensitized solar cell module prepared in Example 2 is 5.18%, and the photoelectric conversion efficiency of the dye-sensitized solar cell module prepared in Comparative Example 1 is 4.04%. Compared with the pure PEO solid electrolyte, the photoelectric conversion efficiency increases by about 1% after adding β-cyclodextrin. It can be seen that β-cyclodextrin can promote the rapid movement of iodine ions, and is used in the all-solid-state light energy storage integrated device of the present invention, so that the integrated device also has a higher photoelectric conversion efficiency.

[0093] Figure 6 The infrared analysis spectra of the photoelectric conversion all-solid electrolyte prepared in Example 2 and Comparative Example 1 are shown in the figure: the horizontal axis Wave number represents the wave number, and the vertical axis Intensity represents the peak intensity. Figure 6 It can be seen that, compared with the solid electrolyte of Comparative Example 1, due to the addition of β-cyclodextrin, the PEO electrolyte membrane in Example 2 will be cross-linked to form a hydrogen bond network structure, thereby accelerating ion migration and improving photoelectric conversion efficiency.

[0094] Figure 7 and Figure 8The scanning electron microscope images of the photoelectric conversion all-solid-state electrolytes prepared in Comparative Example 1 and Example 2 respectively show that the membrane surface of Example 2 is smoother and more uniform than that of Comparative Example 1, and its microstructure is also more delicate and smooth, which will bring more ion transmission channels and enhance the photoelectric conversion efficiency and operation time.

[0095] Fig. 9 The cross-sectional scanning electron microscope image and energy spectrum analysis diagram of the photoelectric conversion all-solid electrolyte prepared in Example 2 are shown in FIG. Fig. 9 It can be seen that the elements of the electrolyte are composed of iodine, oxygen, and carbon, and the elements are evenly distributed. After adding β-cyclodextrin, the solid electrolyte membrane formed is evenly distributed, which is conducive to ion transmission.

[0096] Fig.10 and Fig.11 These are scanning electron microscope images of the counter electrode prepared in Example 2 before and after coating with carbon-sulfur materials. It can be seen that the nickel foam not coated with carbon-sulfur materials has a clear and complete structure, with well-arranged pores and an obvious network structure. The porous structure is conducive to the transmission of ions. After coating with carbon-sulfur materials, the pores in the nickel foam are tightly filled, relatively smooth and flat, and well-arranged, which is conducive to the transmission of holes or ions.

[0097] Fig.12 The cross-sectional scanning electron microscope image and energy spectrum analysis diagram of the electrode prepared in Example 2 are shown in FIG. Fig.12 It can be seen that the elements of the electrode are composed of nickel, sulfur, and carbon, and the distribution of each element is uniform, which means that the coated carbon-sulfur material is in close contact with the nickel foam, which is conducive to the transmission of holes or ions.

[0098] Fig.13 and Fig.14 The long cycle performance diagrams of the lithium-sulfur battery modules prepared in Example 3 and Comparative Example 2 at current densities of 0.1C and 0.2C (1C = 1675mA / g) respectively, in which the horizontal and vertical scales Cycle Number represent the number of cycles, the left vertical coordinate Capacity represents the discharge specific capacity, and the right vertical coordinate coulombic efficiency represents the coulombic efficiency. It can be seen that the all-solid electrolyte prepared by adding β-cyclodextrin in Example 3 exhibits excellent electrochemical properties. In the application of lithium-sulfur batteries, when the current density is 0.1C, a reversible specific capacity of 1229.1mAh / g can be obtained; when the current density is 0.2C, a reversible specific capacity of 871.1mAh / g can be obtained; and it has good cycle stability. However, since the all-solid electrolyte of Comparative Example 2 does not add β-cyclodextrin, in the application of lithium-sulfur batteries, when the current density is 0.1C, only 845.5mAh / g of reversible specific capacity is obtained; when the current density is 0.2C, only 612.59mAh / g of reversible specific capacity is obtained, and the electrochemical performance is far inferior to that of Example 3.

[0099] Fig.15 The constant current charge and discharge test results of the lithium-sulfur battery modules prepared in Example 4 and Comparative Example 3 are shown in the figure. The horizontal and vertical scales Specific Capacity represent the specific capacity, and the vertical scale Voltage represents the voltage. Fig.15 It can be seen that the lithium-sulfur battery module using Ketjen black and carbon nanotubes as carbon sources in Example 4 is significantly better than the battery using acetylene black in Comparative Example 3 in terms of performance, which is mainly due to the fact that Ketjen black and carbon nanotubes have better conductivity and structural properties. Although both carriers are nickel foam, the special structure of Ketjen black and carbon nanotubes is more suitable for the three-dimensional porous structure of nickel foam, further optimizing the electronic conduction network and forming a more efficient charge transfer channel. This improvement not only enhances the conductivity of nickel foam, but also provides more active sites, promotes the efficient conversion of sulfur from LiPSs to Li2S2 / Li2S near 2.32V, and significantly reduces potential polarization and voltage gap. The test results show that the voltage gap of Example 4 is 105mV smaller than that of Comparative Example 4, further verifying the advantages of Ketjen black and carbon nanotubes in improving the overall performance of lithium-sulfur batteries.

[0100] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. An all-solid-state optical energy storage integrated device, characterized in that: From bottom to top, it includes energy storage electrode, energy storage all-solid electrolyte, compatible electrode, photoelectric conversion all-solid electrolyte and dye-sensitized photoanode; The compatible electrode includes nickel foam and a carbon-sulfur composite material coated on the nickel foam, the raw materials for preparing the energy storage all-solid-state electrolyte include polyethylene oxide, lithium bis(trifluoromethanesulfonyl)imide and β-cyclodextrin, the raw materials for preparing the photoelectric conversion all-solid-state electrolyte include polyethylene oxide, elemental iodine, lithium iodide and β-cyclodextrin, and the energy storage electrode is a lithium metal anode.

2. The all-solid-state optical energy storage integrated device according to claim 1, characterized in that: The method for preparing the compatible electrode comprises the following steps: (1) mixing a sulfur source, a carbon source and polyvinylidene fluoride in a first organic solvent and grinding the mixture to obtain a slurry; (2) Apply the slurry to the foam The compatible electrode is obtained by sequentially performing heat treatment and compaction treatment.

3. The method for preparing a compatible electrode according to claim 2, characterized in that: In step (1), the sulfur source includes sublimated sulfur; and / or the carbon source includes Ketjen black and carbon nanotubes; and / or the first organic solvent includes N-methylpyrrolidone.

4. The method for preparing a compatible electrode according to claim 2 or 3, characterized in that: In step (1), the mass ratio of the sulfur source, the carbon source and the polyvinylidene fluoride is (6-8):(1-3):1; and / or the mass volume ratio of the polyvinylidene fluoride to the first organic solvent is 1 g:(4-6) mL.

5. The method for preparing a compatible electrode according to claim 2, characterized in that: In step (2), the heat treatment is performed at 70-90° C. for 10-14 hours; and / or the compaction treatment pressure is 5-15 MPa.

6. The all-solid-state optical energy storage integrated device according to claim 1, characterized in that: The preparation method of the photoelectric conversion all-solid electrolyte comprises the following steps: Elemental iodine and lithium iodide are dissolved in a second organic solvent, then beta-cyclodextrin is added and mixed, and then polyethylene oxide is added, stirred under heating conditions, and dried to obtain the photoelectric conversion all-solid electrolyte.

7. The all-solid-state optical energy storage integrated device according to claim 6, characterized in that: The second organic solvent comprises acetonitrile; And / or, the raw materials for preparing the photoelectric conversion all-solid electrolyte include, by weight: 0.5-2 parts of elemental iodine, 3-8 parts of lithium iodide, 1-2 parts of β-cyclodextrin, and 6-9 parts of polyethylene oxide; and / or, the mass volume ratio of the polyethylene oxide to the second organic solvent is 1 g: (8-12) mL; And / or, the heating condition is stirring at 50-70° C. for 4-6 hours.

8. The all-solid-state optical energy storage integrated device according to claim 1, characterized in that: In the raw materials for preparing the energy storage all-solid electrolyte, the mass ratio of polyethylene oxide, lithium bis(trifluoromethanesulfonyl)imide and beta-cyclodextrin is 1:(0.2-0.4):(0.1-0.3).

9. A method for preparing the all-solid-state optical energy storage integrated device according to any one of claims 1 to 8, characterized in that: The following steps are involved: The energy storage electrode, the energy storage all-solid electrolyte, the compatible electrode, the photoelectric conversion all-solid electrolyte and the dye-sensitized photoanode are stacked and assembled from bottom to top to obtain the all-solid-state optical energy storage integrated device.

10. Application of the all-solid-state integrated optical energy storage device according to any one of claims 1 to 8 in portable electronic devices or wearable devices.